Returning through Front or Back Door: Legibility Sorter for Overseas Ph.D. Holders in Kazakhstan - Kuzhabekova, Aliya (Journal of International Students, 2024)
The article reports the results of an interview-based study exploring how internationally educated Ph.D. degree holders re-integrate into research environment in Kazakhstan and how the process of reintegration varies depending on the country of study. We found that returnees from non-Western countries experience greater challenges than returnees from the Western contexts. Applying the concept of “legibility” we reveal that the variation in the experiences is the result of operation of a legibility sorting mechanism used by the state in valuation of the quality of doctoral education of two formerly colonial academic systems – the post-Soviet and the Western one, which compete as they exert neo-colonial claims on the academic system in Kazakhstan. The state uses foreign degree recognition mechanism as a heterogeneity producing system signalling the stakeholders the desired perception of the value of the different degrees. The differentiation in the experiences results from the sorting.